Synthesis and optical characterization of Er-doped bismuth titanate nanoparticles grown by sol–gel hydrothermal method. Issue 4 (March 2017) - Fuentes, S.; Muñoz, P.; Llanos, J.; Vega, M.; Martin, I.R.; Chavez-Angel, E.
Abstract: The Er 3+ -doped bismuth titanate (Bi4 Ti3 O12, BIT) nanoparticles were synthesized by a combined sol–gel and hydrothermal method under a partial oxygen pressure of 30 bar. The composition and morphology were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Raman scattering. They showed pure and homogeneous spherical BIT nanoparticles with a size below the 30 nm. The incorporation of Er ions showed a strong decrease in the lattice parameters, as well as averaged particle size. The photoluminescence up-conversion (excitation wavelength =1480 nm) showed an enhancement of the infrared emission (980 nm) as Er concentration increased, achieving a maximum for 6% mol, while photoluminescence spectra (excitation wavelength =473 nm) showed a strong green emission (529 and 553 nm) with a maximum at 4% mol.